Profitability of Three Vegetables In Aonla Based Multistoried Agroforestry System - Miah, MMU; Ahamed, T; Reza, A; Pingki, LS (Annals of Bangladesh Agriculture, 2022)
Aonla based multistoried agroforestry with vegetables is a promising solution to mitigate the devastating effects of climate change by offering multidimensional benefits. However, Bangladeshi farmers are less aware and equipped. about the cultivation techniques and benefit of multistory agroforestry production systems. Therefore, the present study was aimed to assess the yield potentiality and profitability of aonla based multistoried vegetables production system during the period of November 21 to March 22. Three individual experiments each for tomato, eggplant and potato were laid out in a single factor Randomized Complete Block Design (RCBD) with three replications. Upper storied plant aonla received 100% Photosynthetically Active Radiation (PAR), but incident light was gradually decreased on middle storied (carambola, lemon, dragon fruit) and lower storied (vegetables) in multistoried conditions. The vegetables experienced 50, 78, 98, and 100% PAR in T1 (Multistoried), T2 (Aonla + Dragon fruit + Vegetables), T3 (Dragon fruit + Vegetables) and T4 (Sole cropping of vegetables) treatment, respectively. Considering the yield of tested vegetables in heaviest shade (T1), suitability rank was eggplant > tomato > potato. The per plant yield reduction was also high in T1 such as potato (40.47%) > tomato (34.29%) > eggplant (33.17%). A positive polynomial (for tomato) and linear (for eggplant and potato) relationship was found between yield and light (% PAR). BCR of dragon fruit + eggplant based system 5.02 was found quite profitable. When both BCR and LER were taken into account, the aonla + dragon fruit + eggplant agroforestry system was found the best production technique for production diversification, maximum land use efficiency, and better profitability. Ann. Bangladesh Agric. (2022) 26 (1) : 49-60